Evaluation of Selected Plant Essential Oils for Aphid Pest Control in Integrated Pest Management - José Luis Casas; María López Santos-Olmo; Aitor Sagarduy-Cabrera; Mᵃ Ángeles Marcos-García (Insects)
Aphids are major agricultural pests, feeding on plant sap and transmitting viruses to economically important crops. The use of synthetic pesticides is increasingly restricted due to stricter regulations aimed at protecting both human and environmental health. To address this challenge, we investigated the potential of essential oils (EOs) extracted from rosemary (Salvia rosmarinus Spenn.), laurel (Laurus nobilis L.), and cypress (Cupressus sempervirens L.) as alternatives to synthetic insecticides, while ensuring compatibility with biological control strategies. The EOs were extracted via hydrodistillation, diluted in acetone, and tested against the aphid Myzus persicae and its natural predator, the hoverfly (Sphaerophoria rueppellii). Aphid mortality was dose-dependent, reaching 85% with rosemary EO, 83% with laurel, and 81% with cypress. In contrast, hoverfly larvae mortality remained low, with a maximum of 20%, which could largely be attributed to the solvent used in the assays. These promising results support further research to develop effective EO-based tools for integrated pest management.